Композиційні властивості малих залізничних вокзалів Галичини ХІХ – початку ХХ століть - Рочняк, Ю. А. (Publishing House of Lviv Polytechnic National University, 2014)
Виявлено головні композиційні ознаки низки малих залізничних вокзалів ХІХ – поч. ХХ-го століть сучасної Галичини, сформульовані стилістичні типи, розташування в краю. Small railway station buildings of modern Galicia (Halytchyna) built in 19th – at the beginning of 20th century and located within the boundaries of Lviv, Ternopil, and Ivano-Frankivsk regions of Ukraine comprise the majority of the existing railway station buildings. They have a pronounced composition and style, and form an important heritage of civil architecture, requiring deep research, protection and adaption to the needs of nowadays. We found out common features in the location of railway stations with respect to tracks, organization of the adjacent territory of these buildings, as well as dominant transversal and prevailing longitudinal symmetry of these buildings. The paper outlines main compositional and stylistic types of small railway station buildings: Round-arc type (stations Stare Selo, Kolomyia, Zabolotiv), Rustic-roof type (stations Sykhiv, Mykulytchyn, Vorokhta, Hrebeniv, Tukhla, Yasenytsia, Turka, Kopytchyntsi, Terebovlia, Zhydatchiv, Rohatyn etc.), Podillia type (stations Vyhnanka, Bila-Tchortkivska, Yahilnytsia, Tovste, Borshtchiv, Ivane-Puste), Sambir type (stations Komarno, Rudky, Staryi Sambir, Strilky), Mostyska type (stations Mshana, Sudova Vyshnia, Mostyska-I, Khyriv), Rava type (stations Kulykiv, Zashkiv, Hlynske, Dobrosyn), Pavilion-like type (stations Bovshiv, Bortnyky). Location of these types by the name of the locality or direction of tracks makes them especially important from the point of view of the identity of regions. Attention is paid to the scattering of Rustic-roof type and peculiar penetration of Round-arc (stations Luzhany, Hlyboka-Bukovynska, Vadul-Siret, Sutchava/Suceava Nord) and Podillia types (stations Vyzhnytsia/Wiżnitz, Stefaneshty/Stefaneşti) in Bucovina (Bukovyna). Initially build in the form of a dwelling house, small railway station buildings evolved into an independent architectural type and are similar to analogous buildings of Danube Monarchy and other countries of the Central Europe. A part of the objects is in bad condition, some of them have been drastically degrading recently (stations Hlibovytchi, Dilatyn, Tatariv). Their protection is not possible without professional reasoning, public activity, and political will.